Muscle damage protective effect by two maximal isometric contractions on maximal eccentric exercise of the elbow flexors of the contralateral arm. (30th January 2018) - Chen, T. C.; Lin, M. J.; Chen, H. L.; Lai, J. H.; Yu, H. I.; Nosaka, K.
Abstract : Muscle damage after 30 maximal eccentric contractions of the elbow flexors (30MVEC) is reduced when the same exercise is performed by the opposite arm, and when two maximal voluntary isometric contractions at a long muscle length (2MVIC) are performed prior to 30MVEC by the same arm. This study investigated the hypothesis that 2MVIC would attenuate muscle damage after 30MVEC performed by the opposite arm. Untrained young (20‐25 years) men were placed into 1 of 4 experimental groups that performed 2MVIC at 1 (1d), 2 (2d), 4 (4d), or 7 days (7d) before 30MVEC by the opposite arm, or one control group that performed 30MVEC only (n = 13/group). Changes in indirect muscle damage markers after 30MVEC were compared among the groups by mixed‐design two‐way ANOVA. Maximal voluntary concentric contraction torque, range of motion, plasma creatine kinase activity, and muscle soreness did not change significantly after 2MVIC. Changes in these variables after 30MVEC were smaller ( P < .05) for 1d (eg, peak soreness: 45 ± 21 mm) and 2d groups (46 ± 20 mm) than control group (66 ± 18 mm), without significant differences between 1d and 2d groups. No significant differences in the changes were found among 4d, 7d, and control groups, except for soreness showing smaller ( P < .05) increases for 4d group (54 ± 19 mm) than 7d (62 ± 17 mm) and control groups. These results supported the hypothesis and showed that muscle damage induced by 30MVEC was reduced by 2MVIC performed 1‐2 days prior to 30MVIC by the contralateral arm.